1991
DOI: 10.1103/physrevb.44.925
|View full text |Cite
|
Sign up to set email alerts
|

Absence of fractional giant Shapiro steps in diagonal Josephson-junction arrays

Abstract: When rf and dc bias currents are injected diagonally into an NxM Josephson-junction array and a

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
6
0

Year Published

1993
1993
2014
2014

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(6 citation statements)
references
References 10 publications
0
6
0
Order By: Relevance
“…Motivated by significant advances in microfabrication techniques of Josephson junction (JJ) arrays, many contemporary studies have focused on understanding the dynamic response of two-dimensional JJ arrays [1][2][3][4][5][6][7]. One type of array with well-defined uniform properties is made of superconducting-normal-superconducting (SNS) proximity effect junctions.…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…Motivated by significant advances in microfabrication techniques of Josephson junction (JJ) arrays, many contemporary studies have focused on understanding the dynamic response of two-dimensional JJ arrays [1][2][3][4][5][6][7]. One type of array with well-defined uniform properties is made of superconducting-normal-superconducting (SNS) proximity effect junctions.…”
mentioning
confidence: 99%
“…Several novel collective locked-in states have been discovered which are manifested in the current versus voltage (IvsV ) characteristics as plateaus. These giant Shapiro steps are a macroscopic manifestation of diverse underlying collective vortex oscillating states [1][2][3][4][5].…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…The circuit consists of the usual Josephson current I c sinφ in parallel with a conductance G. In addition, it has as inputs a dc source current I 0 and an rf source current I s cos ω s t, with the total source current I given by IðtÞ 5 I 0 1 I s cos ω s t: for comparison. This staircase pattern, which is referred to as Shapiro steps (Eikmans and van Himbergen, 1991;Shapiro, 1963;Yu et al, 1992), has been reported by many observers (e.g., Kriza et al, 1991;Kvale and Hebboul, 1991;Larsen et al, 1991;Lee et al, 1991;Sohn et al, 1991).…”
Section: E Inverse Ac Josephson Effectmentioning
confidence: 88%
“…This interpretation was successfully verified in numerical simulation modelling of the arrays by a resistively shunted junction (RSJ) model 7,8 , as well as from analytic studies 9 . There have also been some experimental 10 and theoretical studies 11,12,13 of the relevance of the geometry of the arrays and the direction of the input current on the generation of fractional GSS. Moreover, the experiments in GSS have encouraged investigations of JJA as coherent radiation sources 14 .…”
Section: Introductionmentioning
confidence: 99%